A history of Sarawak under its two white rajahs, 1839-1908 - Baring-Gould, S. (Sabine) 1834-1924; Bampfylde, C. A. (Silverfish Malaysian classics, 2019)
Borneo was known to the Arabs many centuries ago, and Sinbad the Sailor was fabled to have visited the island. It was then imagined that a ship might be freighted there with pearls, gold, camphor, gums, perfumed oils, spices, and gems, and this was not far from the truth. When Genghis Khan conquered China and founded his mighty Mogul Empire (1206-27), it is possible that he extended his rule over Borneo, where Chinese had already settled. Kublai Khan is said to have invaded Borneo with a large force in 1292; and that a Chinese province was subsequently established in northern Borneo, in which the Sulu islands were included, is evidenced by Bruni and Sulu traditions. The Celestials have left their traces in the name of Kina Balu (the Chinese Widow) given to the noble peak in the north of the island, and of the rivers Kina-batangan (the Chinese river) and Kina-bangun on the east coast of Borneo, and certain jars, mentioned in Chapter I, ornamented with the royal dragon of China, are treasured as heirlooms by the Dayaks. At Santubong, at the mouth of the Sarawak river, Chinese coins dating back to B.C. 600 and 112, and from A.D. 588 and onwards, have been found, with many fragments of Chinese pottery. The name Santubong is itself Chinese, San-tu-bong, meaning the "King of the Jungle" in the Kheh dialect, and the "Mountain of wild pig" in the Hokien dialect.